Strategi Pemasaran Digital di Era 5.0 untuk Meningkatkan Brand Awareness Hotel Lido Lake Resort by MNC Hotel - Pratiwi, Irda Mawar; Suwanda, Bayu Suriaatmaja; Mulyawaty, Siska (Jurnal EMT KITA, 2026)
This study aims to analyze the implementation and effectiveness of the digital marketing strategy based on the Five Pillars of Marketing 5.0 framework to enhance the brand awareness of Hotel Lido Lake Resort by MNC Hotel. Employing a descriptive qualitative method with a case study in Bogor, West Java, the research was conducted during the 2024–2025 period and involved four key informants from the marketing communication division. The main findings indicate that the structured synergy of the Five Pillars of Marketing 5.0 successfully transformed the brand's position from the Brand Recognition stage to the Brand Recall level. This achievement is characterized by the embedding of a strong and specific brand association, the Unique Selling Proposition (USP) “Anti-Traffic Family Holiday Destination,” into the memory of consumers in the Greater Jakarta area (Jabodetabek). Empirically, this effectiveness is confirmed by a 78.7% increase in FIT (Free Independent Travel) bookings from 2024 to 2025. Practically, this study asserts that integrating Marketing 5.0 technology with a human-centric focus is the key to achieving purchase conversion and building a functional brand memory in the digital era.